Main Tectonic Events and Metallogeny of the North China Craton - Zhai, Mingguo; Zhao, Yue; Zhao, Taiping (Springer Geology, 2016)
This book focuses on the metallogeny and main tectonic events of the North China Craton from early Precambrian to Phanerozoic. It covers the Archean crustal growth, Paleoproterozoic rifting-subduction-collision processes, Great Oxidation Event, Meso-Neoproterozoic multiple rifting, Phanerozoic reworking of the North China Craton, as well as metallogeny related to above different processes. The North China Craton is one of the oldest cratons in the world. It has experienced a complex geological evolution since the early Precambrian, and carries important records of secular changes in tectonics and metallogeny. It provides a systematic review and new results on the growth and evolution of the North China Craton and metallogeny. It will be of broad interest to the earth scientists working in the fields of economic geology, geochemistry, and tectonics of the North China Craton and eastern Asian.